Molecular approaches to classify adult renal epithelial neoplasms. (November 2011) - Maj, Magdalena; Wagner, Ludwig
Evaluation of: Powers MP, Alvarez K, Kim HJ, Monzon FA. Molecular classification of adult renal epithelial neoplasms using microRNA expression and virtual karyotyping. Diagn. Mol. Pathol. 20(2), 63–70 (2011). Novel reliable techniques for the exact classification of renal epithelial neoplasms, especially in cases with morphological ambiguity, are of high importance for diagnosis and patient treatment. Evaluation of gene-expression alterations in various malignancies by array screens and quantitative PCR is a well-known procedure. In this direction, the use of molecular methods, such as virtual karyotyping and miRNA profiling, represents a rather novel approach. In particular, great promise for reliable and specific characterization of renal tumor subtypes, such as clear cell renal cell carcinoma (RCC), papillary RCC, chromophobe RCC and oncoytoma, is offered – according to the recently presented work by Powers et al. – by a miRNA-profiling method. This technique might be used in the form of a clinically applicable biomarker diagnostic tool. In addition, researchers suggest that miRNAs might have a functional role and might therefore contribute to the progress towards personalized cancer therapy. In this article, a broader overview of recent approaches to classify renal epithelial neoplasms is presented, with a focus on promising miRNA gene-expression profiling. The latter needs further elaboration and testing with a larger sample number.